2012
DOI: 10.1111/j.1549-0831.2012.00094.x
|View full text |Cite
|
Sign up to set email alerts
|

Off‐farm Work among Rural Households: A Case Study in theBrazilianAmazon

Abstract: This article analyzes off‐farm work among subsistence‐level farmers in the Santarém region of the Brazilian Amazon. We build on the literature on rural livelihoods in the Global South by exploring how the opportunity to work off the farm is embedded in social relationships. We additionally differentiate our analysis by type of off‐farm work, and examine how other characteristics such as human capital, the available labor supply, and access to infrastructure vary by work outcome. In general, the factors that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 33 publications
1
19
0
1
Order By: Relevance
“…In a qualitative analysis on the Brazilian Amazon, for example, Steward (2007) noted that young people prefer off-farm jobs emainly in the public sector-to agricultural jobs, the returns to which are considerably lower due to low market prices, lack of credit and lack of extension services. VanWey and Vithayathil (2013) found that the likelihood of taking part in off-farm work is higher for males, those more educated, and those residing closer to urban areas.…”
Section: Literature Reviewmentioning
confidence: 95%
“…In a qualitative analysis on the Brazilian Amazon, for example, Steward (2007) noted that young people prefer off-farm jobs emainly in the public sector-to agricultural jobs, the returns to which are considerably lower due to low market prices, lack of credit and lack of extension services. VanWey and Vithayathil (2013) found that the likelihood of taking part in off-farm work is higher for males, those more educated, and those residing closer to urban areas.…”
Section: Literature Reviewmentioning
confidence: 95%
“…She argues that family ties in this context generally serve as information on low-paying agricultural or construction opportunities, while community ties to other young migrants offer information on higher wage opportunities in cities. In addition, a study among smallholder farmers in rural Santarém finds that individuals with a close family member or friend working off of the farm have increased likelihoods of finding off-farm work (VanWey and Vithayathil 2012) and a study in the Ecuadorian Amazon finds that the number of migrants within an individual’s household strongly predicts one’s likelihood of migration (Barbieri et al 2009). These studies indicate that close extra-local networks influence labor mobility in the Amazon region, and we suggest that part of the variation in information provided by family ties reflects the life course nature of networks.…”
Section: Theoretical Framework and Conceptual Modelmentioning
confidence: 99%
“…Inspirado em estudos similares desenvolvidos no contexto amazônico VITHAYATHIL, 2013;LOMBARDI et al, 2015;GUEDES et al, 2017), este trabalho analisa como a composição demográfica e o tempo de residência das famílias de pequenos agricultores se relacionam com a intensidade observada do desmatamento em assentamentos agrícolas na Amazônia. Para tanto, foram utilizados dados sobre os colonos do Projeto de Assentamento Machadinho d'Oeste, no estado de Rondônia.…”
Section: Introductionunclassified